MENINGKATKAN PERILAKU DISIPLIN PESERTA DIDIK MELALUI BERMAIN PERAN PADA ANAK USIA 5-6 TAHUN DI TK ADSIKRA - Rusmini '; Mahdum '; Hukmi ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Based on field observations researchers found several problems kindergartner Adzikra Sungai Buluh District of Singingi Hilir Regency Kuantan Singingi, that the child may not know the manners and decorum, children also do not follow school rules, the child does not follow the dress prescribed, as they use slippers at a time not specified schedule, always grab the child and would not carry out orders and the advice of teachers to orderly. To cope with the behavior of the child discipline, we need a way or a new method that is expected to address the behavior of the child discipline one is to play the role. This study aims to determine the increase of discipline behavior of learners through play a role in children age 5-6 years in kindergarten Adzikra Sungai Buluh Singingi Hilir Subdistrict Regency Kuantan Singingi. The number of subjects in this study were 15 children. The data collection techniques were used that observation. This study includes quantitative and qualitative research. Quantitatively, the data were analyzed descriptively percentage. Level changes measured by percent, while qualitatively explain the activities of children and teachers obtained through observation, interviews and performance during the study. The study hypothesis is through role play can improve discipline the behavior of children aged 5-6 years. It can be seen from the analysis of data obtained before disciplinary action behavior of children the average is 22.50, with a percentage of the ideal score of 37.50%, Start Developing criteria (MB). In the first cycle of action, the results amounted to 55.65% didapatlah developing criteria to expectations (BSH). Improvement of cycle 1 of the initial data is 48%. Meanwhile, for the activities of teachers in cycle 1 is located on the criteria Enough with the average value of 40.00%, and the activities of children in activities play a role in cycle 1 is located on the criteria please with an average 40.00%. Furthermore, in cycle 2 didapatlah yield was 64.17% developing criteria to expectations (BSH). Improvement of cycle 2 of cycle 1 was 25%. While the improvement that occurred in cycle 2 when compared with the initial data that is equal to 86%. So this study should not be continued again for the next cycle.